2021
DOI: 10.1371/journal.pgen.1009653
|View full text |Cite
|
Sign up to set email alerts
|

Neofunctionalization of a second insulin receptor gene in the wing-dimorphic planthopper, Nilaparvata lugens

Abstract: A single insulin receptor (InR) gene has been identified and extensively studied in model species ranging from nematodes to mice. However, most insects possess additional copies of InR, yet the functional significance, if any, of alternate InRs is unknown. Here, we used the wing-dimorphic brown planthopper (BPH) as a model system to query the role of a second InR copy in insects. NlInR2 resembled the BPH InR homologue (NlInR1) in terms of nymph development and reproduction, but revealed distinct regulatory rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 72 publications
(116 reference statements)
1
25
0
Order By: Relevance
“…Methods for efficient macromolecule delivery are essential to any CRISPR genome-editing system and the delivery strategy can be a substantial technological hurdle preventing deployment in target organisms. While temporally delayed by 3 to 5 years relative to the gene-editing advances in D. melanogaster , mosquitoes, the Lepidoptera, and the Coleoptera, CRISPR/Cas9-editing is now reported for nine species of Hemiptera with a total of 17 different genes being targeted ( Tables 2 – 4 ) ( Xue et al, 2018 ; Kotwica-Rolinska et al, 2019 ; Le Trionnaire et al, 2019 ; Zhao et al, 2019 ; Cagliari et al, 2020 ; Heu et al, 2020 ; Reding and Pick, 2020 ; Klobasa et al, 2021 ; Xue et al, 2021 ; Heu et al, 2022 ; Pacheco et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Methods for efficient macromolecule delivery are essential to any CRISPR genome-editing system and the delivery strategy can be a substantial technological hurdle preventing deployment in target organisms. While temporally delayed by 3 to 5 years relative to the gene-editing advances in D. melanogaster , mosquitoes, the Lepidoptera, and the Coleoptera, CRISPR/Cas9-editing is now reported for nine species of Hemiptera with a total of 17 different genes being targeted ( Tables 2 – 4 ) ( Xue et al, 2018 ; Kotwica-Rolinska et al, 2019 ; Le Trionnaire et al, 2019 ; Zhao et al, 2019 ; Cagliari et al, 2020 ; Heu et al, 2020 ; Reding and Pick, 2020 ; Klobasa et al, 2021 ; Xue et al, 2021 ; Heu et al, 2022 ; Pacheco et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two insulin receptor genes ( NlInR1 and NlInR2 ) from N. lugens were targets of CRISPR/Cas9 mutagenesis ( Tables 2 – 4 ) ( Zhao et al, 2019 ; Xue et al, 2021 ). Previous studies showed that RNAi silencing of NlInR1 and NlInR2 controls wing polyphenism (short versus long wings, respectively), which is important for N. lugens dispersal ( Xu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations